Association of adiposity, measured by skinfold thickness, with parental history of diabetes in a South Indian population: data from CURES-114. Issue 1089 (25th February 2016) - Surendar, J; Indulekha, K; Deepa, M; Mohan, V; Pradeepa, R
Abstract : Purpose of the study: To look at the association of central and peripheral skinfold thickness with parental history of diabetes in subjects without diabetes. Methods: Subjects with no parental history of diabetes (n=1132), subjects with one parent with diabetes (n=271) and subjects with both parents with diabetes (n=51) were recruited from the Chennai Urban Rural Epidemiological Study (CURES) conducted between 2001 and 2003. Biceps, triceps, medial calf, mid-thigh, chest, abdomen, mid-axillary, suprailiac and subscapsular sites were measured with Lange skinfold callipers. Results: Trunk fat measurements, such as chest (p=0.020), mid-axillary (p=0.005), suprailiac (p=0.014), subscapsular (p<0.001) and abdomen (p=0.010) skinfolds, were highest in subjects with both parents with diabetes followed by those with one parent with diabetes, and lowest in those with no parental history of diabetes. However, the peripheral fat measurements, ie, biceps, triceps, medial calf and mid-thigh, were not significantly different between the study groups. Total truncal and peripheral fat skinfold thicknesses showed a significant positive association with other indices of obesity such as body mass index (BMI) and waist circumference in relation to trunk fat (BMI: r=0.748, p<0.001; waist: r=0.776, p<0.001) and peripheral fat (BMI: r=0.681, p<0.001; waist: r=0.569, p<0.001). Conclusions: A significant association was observed between truncal and peripheral fat, assessed by skinfold thickness, and parental history of diabetes among subjects without diabetes in this urban South Indian population.